Development and Evaluation of a New Predictive Nomogram for Predicting Risk of Herpes Zoster Infection in a Chinese Population with Type 2 Diabetes Mellitus - Zeng N (Dove Medical Press, 2021)
Ni Zeng,1,2 Yueyue Li,2 Qian Wang,3 Yihe Chen,2 Yan Zhang,1 Lanfang Zhang,1 Feng Jiang,4,5 Wei Yuan,1 Dan Luo2 1Department of Dermatology, Affiliated Hospital of Zunyi Medical University,149 Dalian Road, Huichuan District, Guizhou, 563003, People’s Republic of China; 2Department of Dermatology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, 210000, People’s Republic of China; 3Department of Endocrinology, Affiliated Hospital of Zunyi Medical University, Guizhou, 563003, People’s Republic of China; 4Neonatal Department, Obstetrics and Gynecology Hospital of Fudan University, Shanghai, 200011, People’s Republic of China; 5Department of Pediatrics, The First Affiliated Hospital of Nanjing Medical University, Nanjing, 21000, People’s Republic of ChinaCorrespondence: Wei YuanDepartment of Dermatology, Affiliated Hospital of Zunyi Medical University, 149 Dalian Road, Huichuan District, Guizhou, 563003, People’s Republic of ChinaTel/Fax +86 13655187928Email dryuanweihua@sina.comDan LuoDepartment of Dermatology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, 210000, People’s Republic of ChinaTel/Fax +86 13655187928Email daniluo2005@163.comPurpose: To identify potential risk factors for herpes zoster infection in type 2 diabetes mellitus in southeast Chinese population.Patients and Methods: We built a model involving 266 herpes zoster patients collecting data from January 2018 to December 2019. The least absolute shrinkage and selection operator (Lasso) predictive model was used to test herpes zoster virus risk using the patient data. Multivariate regression was conducted to decide which variable would be the strongest to decrease the Lasso penalty. The predictive model was tested using the C-index, a calibration plot, and decision curve study. External validity was verified by bootstrapping by counting probabilities.Results: In the prediction nomogram, the prediction variables included age, sex, weight, length of hospital stay, infection, and blood pressure. The C-index of 0.844 (0.798– 0.896) indicated substantial variability and thus the model was adjusted appropriately. A score of 0.825 was achieved somewhere in the above interval. Examination of the decision curve estimated that herpes zoster nomogram was useful when the intervention was determined at the 16 percent of the herpes zoster infection potential threshold.Conclusion: The herpes zoster nomogram combines age, weight, position of the rash, 2-hour plasma glucose, glycosuria, serum creatinine, length of the hospital stay, and hypertension. This calculator can be used to assess the individual herpes zoster risks in patients diagnosed with type 2 diabetes mellitus.Keywords: glycemic status, herpes zoster, nomogram, type 2 diabetes mellitus, infection